Moritz Hartmann, Bohemia and the Metternich System - Bourke, Eoin (. Jahrbuch. - Bielefeld : Aisthesis Verlag, 2001-. - Online-Ressource 9.2003, 2004)
Hartmann and his Prague friends, whether German-Gentile or German-Jewish, rallied enthusiastically to the cause of what at first was a reawakening of suppressed Bohemic cultural nationalism and a move towards across-fertilisation of the two main lingual cultures (Czech/German) andthe three main ethnicities (Czech/German/Jewish) of the country. They soon saw themselves as a "Jungböhmische Bewegung" to correspond to Young Germany. The Prague writer Rudolf Glaser founded a literary journal called 'Ost und West' for the express purpose of bringing together German and Slavic literary impulses under the Goethean motto: "Orient und Occident sind nicht mehr zu trennen". With Bohemia as the bridge, 'Ost und West' published German translations from all the Slavic languages including Pushkin and Gogol, contributions by German writers sympathetic to the cause of emerging nations like Heinrich Laube, Ferdinand Freiligrath, Ernst Willkomm, but above all the Prague circle of Young Bohemians like Alfred Meissner, Isidor Heller, Uffo Horn, Gustav Karpeles and Ignatz Kuranda. Also Hartmann made his literary debut in the journal with a love poem entitled "Der Drahtbinder", and featuring a subtitle which was in keeping with the spirit of the times: "nach einem slavischen Lied".